Design and implementation of IoT gas meter based on security chip. Issue 1 (1st November 2022) - Xu, Xiaoqing; Liang, Xiaowei; Shen, Cheng
Abstract: IoT gas meter is facing the challenge of information security. This paper designs and implements a scheme of gas meter based on security chip. The scheme uses stm32l073 as MCU to collect gas metering data, cooperates with Hua Hong's security chip, and uses NB_IoT as the communication module. The business data is pushed to the gas meter business management system through China Telecom Tianyi IoT platform CTWing, so as to realize the remote safety management of gas meters.